2022
DOI: 10.1016/j.clinthera.2021.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Projecting the Long-term Clinical Value of Mavacamten for the Treatment of Obstructive Hypertrophic Cardiomyopathy in the United States: An Assessment of Net Health Benefit

Abstract: Purpose:The aim of the study was to project the long-term net health benefits of mavacamten for the treatment of symptomatic obstructive hypertrophic cardiomyopathy (HCM) in the United States.Methods: A Markov model with 4 mutually exclusive health states (New York Heart Association [NYHA] functional classes I, II, and III/IV and death) was developed to project the life-years (LYs) and quality-adjusted life-years (QALYs) over a lifetime horizon for patients with symptomatic obstructive HCM receiving mavacamten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
0
9
0
2
Order By: Relevance
“…We found relevant citations describing 2 distinct phase II trials (PIONEER-HCM and MAVERICK-HCM), 2 phase III trials (EXPLORER-HCM and VALOR-HCM), substudies of EXPLORER-HCM, and 2 modeling studies. [4][5][6][7][8][9][10][11] The results of the VALOR-HCM are currently only available in abstract form with a late breaking clinical trial report on April 2, 2022 at the American College of Cardiology meeting. 9 We also reviewed review articles on HCM and mavacamten that were identified through this search process and those identified through backwards citation tracking of other citations.…”
Section: Search Strategy and Included Citationsmentioning
confidence: 99%
See 4 more Smart Citations
“…We found relevant citations describing 2 distinct phase II trials (PIONEER-HCM and MAVERICK-HCM), 2 phase III trials (EXPLORER-HCM and VALOR-HCM), substudies of EXPLORER-HCM, and 2 modeling studies. [4][5][6][7][8][9][10][11] The results of the VALOR-HCM are currently only available in abstract form with a late breaking clinical trial report on April 2, 2022 at the American College of Cardiology meeting. 9 We also reviewed review articles on HCM and mavacamten that were identified through this search process and those identified through backwards citation tracking of other citations.…”
Section: Search Strategy and Included Citationsmentioning
confidence: 99%
“…A Markov model with 4 mutually exclusive health states (NYHA functional class I, II, III/IV, or death) was conducted by Desai and colleagues 11 using the 30-week effects seen in EXPLORER-HCM to extrapolate the impact on final health outcomes over a lifetime. As such, patients could receive overlapping therapy with β-blockers or non-dihydropyridine calcium channel blockers along with mavacamten or placebo.…”
Section: Modeling/economic Evaluationmentioning
confidence: 99%
See 3 more Smart Citations